Public Perceptions on Land Use Change and Flood Incidence in the Kendal Watershed Area - Andi Irwan Benardi; Atta-Ur Rahman; Dewi Liesnoor Setyowati; Adrian Gustiyansyah Selebes; Joshua Vincent Gerar Yametis; Bayu Wijayanto; Novika Adi Wibowo; Muhammad Zulfi Al'Ghani (JURNAL GEOGRAFI, 2026)
Uncontrolled land-use changes driven by rapid population growth and expanding residential development have significantly heightened flood risk in the Kendal Watershed, Kendal District. The conversion of agricultural and open land into built-up areas has altered hydrological processes, reducing water infiltration capacity and increasing surface runoff. This study aims to (1) identify spatial and temporal land-use changes from 2017 to 2025, (2) analyze public perceptions regarding land conversion and flooding, and (3) assess the resulting social and environmental impacts within the watershed area. A quantitative descriptive approach was employed by integrating Geographic Information System (GIS)-based analysis of Sentinel-2A satellite imagery with primary data collected through Likert-scale questionnaires administered to 96 respondents residing in flood-prone areas. The results indicate a substantial decline in rice field areas by 44.19 hectares, accompanied by a notable increase in residential land of 36.12 hectares over the study period. Community perceptions reveal that these land-use changes have contributed to increased flood frequency, greater flood intensity, and longer inundation duration. The observed social impacts include disruptions to daily activities, reduced access to clean water, economic losses, and a higher incidence of waterborne and skin-related diseases. Environmental impacts are reflected in declining sanitation conditions, increased waste accumulation, river sedimentation, and persistent water pollution. These findings underscore the urgent need for stricter land-use regulation, restoration of green and infiltration areas, and adaptive, sustainable spatial planning to reduce flood risk and enhance community resilience in the Kendal Watershed